2020
DOI: 10.1115/1.4045182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Double-Side Labyrinth Seals on Aerodynamic Performance in a Transonic Shrouded Turbine Stage

Abstract: Labyrinth seals on both rotor casing and blade tip as an effective method to control the leakage flowrate of the shroud and improve aerodynamic performances in a transonic turbine stage are investigated in this study. Compared to the case without the labyrinth seal structure, the cases with three different types of sealing teeth have been shown to reduce significantly the tip leakage flow by computational simulations. The double-side sealing teeth case reduces the leakage flowrate mleakage/mpassage from 3.4% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Porreca et al, [10][11][12] Rebholz et al, 13 and Liu 14,15 studied shroud reduction on the turbine blade, by comparing the influences of full and partial shroud structure on leakage flow and turbine performance, improved and optimized partial shroud structures were brought up. Li 16 applied four configurations with or without labyrinth seal arranged on casing and rotor blade tip for computational simulations and found that the double-side labyrinth seal achieved the highest turbine stage efficiency. Wasilczuk et al 17 proposed a seal structure with air curtain through slots fully incorporated within the fin of labyrinth seal on the shroud.…”
Section: Introductionmentioning
confidence: 99%
“…Porreca et al, [10][11][12] Rebholz et al, 13 and Liu 14,15 studied shroud reduction on the turbine blade, by comparing the influences of full and partial shroud structure on leakage flow and turbine performance, improved and optimized partial shroud structures were brought up. Li 16 applied four configurations with or without labyrinth seal arranged on casing and rotor blade tip for computational simulations and found that the double-side labyrinth seal achieved the highest turbine stage efficiency. Wasilczuk et al 17 proposed a seal structure with air curtain through slots fully incorporated within the fin of labyrinth seal on the shroud.…”
Section: Introductionmentioning
confidence: 99%